Effectiveness of interactive learning in teaching fraction concepts to elementary school teacher education students at UKI Toraja - Topanus Tulak; Rubianus; Harmelia Tulak; Desi Natalia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study explores the effectiveness of interactive learning in teaching fraction concepts to students of the Elementary School Teacher Education Program at UKI Toraja. A qualitative approach using a case study method was employed to gain an in-depth understanding of students' experiences during the learning process. Data were collected through observations, interviews, and document analysis, and analysed using Miles and Huberman's interactive model. The findings reveal that interactive approaches promote active student engagement, enhance conceptual understanding, and help address common misconceptions in fractions. These results highlight the importance of contextual, collaborative, and experience-based learning strategies in elementary mathematics education. The study offers implications for designing more meaningful instruction for prospective teachers and contributes to curriculum development based on students learning needs.